Bone mineral changes in young adult females on short-term proton pump inhibitor: A retrospective cohort study: Bone mineral changes in courses of proton pump inhibitor treatment - Kucukdemirci, Omer; Kapucu, Korhan; Mavis, Osman (Journal of Surgery and Medicine, 2024)
Background/Aim: Proton pump inhibitors (PPIs), despite being the most prescribed medications today, have generated controversy due to their potential impact on bone metabolism. Numerous studies have emphasized the potential of prolonged PPI use to reduce bone mineral density, thereby increasing the risk of bone fractures among elderly and young individuals. However, the precise impact of PPI usage for 1 year or less on bone mineral density in young adults remains incompletely understood. Method: In this retrospective cohort study, we conducted a comprehensive review of all dual x-ray bone densitometric examinations conducted on females under 40 years old at our tertiary care center between 2010 and 2014. Among the initial 685 patients assessed, 117 samples met the predefined inclusion criteria and were consequently enrolled in the study. Subsequently, the enrolled cases were categorized into three distinct groups: Group 1 (n=46), which received PPI treatment for less than six months; Group 2 (n=31), which received PPIs for a duration ranging from 6 to 12 months; and Group 3 (n=40), comprising individuals with no history of PPI use, thus serving as the control group. Comprehensive baseline descriptive data, encompassing bone mineral density, t-scores, and z-scores, were meticulously compared among the three groups mentioned above. Results: The overall mean age of the study population was 32.84 (5.27) years, with an age range spanning from 20 to 40 years. No statistically significant differences in age were discerned among the three groups. Similarly, the groups exhibited no significant body mass index (BMI) variations. Noteworthy findings emerged after examining the effects of PPI usage on bone mineral density, z-scores, and t-scores across the three groups. Specifically, the data suggested that PPIs might influence t-scores (Group 1: -0.48 (0.77); Group 2: -1.25 (0.86); Group 3: -0.33 (0.78)), yielding an F-value of 13.28 for (2.116), signifying statistical significance at P<0.001. Moreover, the observed mean square error (MSE) was 64, while the effect size (eta²) was 0.19. Subsequent post-hoc Tukey tests indicated a significant distinction in the T-score of Group 2 compared to the other two groups. Furthermore, the analysis of z-scores (Group 1: 0.46 (0.79); Group 2: -1.27 (0.76); Group 3: -0.35 (0.86)) revealed a similar trend, with an F-value of 13.21 for (2.116) and a P-value below 0.001. The corresponding MSE was 0.65, and the eta² stood at 0.19. Additional post-hoc Tukey tests indicated that the Z-score of Group 2 significantly diverged from the other groups. However, it is noteworthy that both t and z-scores for Group 1 and Group 3 did not exhibit statistically significant differences. Conclusion: Prolonged use of PPIs for durations surpassing 6 months may potentially reduce bone mineral density among young adults. Nevertheless, this observed impact does not attain clinically significant levels of osteopenia. Conversely, using PPIs for periods under 6 months did not significantly affect bone mineral density.